Polymorphism rs3088232 in the BRDT gene is associated with idiopathic male infertility in the West Siberian Region of Russia - A. S. Wainer; V. M. Nagaitsev; O. V. Korolkova; V. V. Vostrikov; L. V. Osadchuk; Ye. V. Pechkovsky; I. S. Malinovskaya; M. L. Filipenko (Бюллетень сибирской медицины)
Allelic variants of genes involved in spermatogenesis can contribute to the genetic predisposition to idiopathic male infertility. In the present study we investigated the association of polymorphism rs3088232 in the BRDT gene with the risk of this pathology on the sample of 105 infertile patients and 230 healthy controls. We revealed the association of allele G (OR = 1.80; CI 1.16—2.80; p = 0.008) and genotype GG (OR = 6.47; CI 1.23—34.15; p = 0.01) with idiopathic male infertility.